Flooring-systems and their interaction with furniture and humans. (2017) - Frier, C.; Pedersen, L.; Andersen, L.V.; Persson, P.
Abstract: Flooring-system designs may be sensitive in terms of their vibrational performance due the risk that serviceability-limit-state problems may be encountered. For evaluating the vibrational performance of a flooring system at the design stage, decisions must be made by the engineer in charge of computations. Passive humans and/or furniture are often present on a floor. Typically, these masses and their way of interacting with the floor mass are ignored in predictions of vibrational behaviour of the flooring system. Utilizing a shell finite-element model, the paper explores and quantifies how non-structural mass can influence central parameters describing the dynamic behaviour of the flooring system with focus on elevated non-structural mass.